2011
DOI: 10.17159/2078-516x/2011/v23i4a324
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertension and the relationship with body composition in Grade 1 learners in the North West Province of South Africa

Abstract: Abstractobjective. To determine the prevalence of hypertension in Grade 1 learners in the North West Province of South Africa and to investigate the association between blood pressure (BP) and body composition of these children. Methods. Data were collected by means of a stratified random sampling procedure from 816 Grade 1 learners (419 boys, 397 girls) with a mean age of 6.78±0.49 years (mean±SD), in the NW-CHILD-study. Height, weight, skinfolds (subscapular, triceps, calf) and waist circumference were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
5
29
1
Order By: Relevance
“…In Africa, low prevalences of HT were reported as 4.9% in Sudan [5] and 4% in Egypt [11]. On the other hand, the rate of 10.1% hypertensive black Bantu Congolese children in this study is intermediate between those from non-Bantu Sudanese and Egyptian children [5, 11] and that of 29.4% black Bantu South African children [6]. These differences are related to standards of developing or emerging economies, overweight/obesity [1719], and ethnic/genetic factors [3, 22].…”
Section: Discussionmentioning
confidence: 60%
“…In Africa, low prevalences of HT were reported as 4.9% in Sudan [5] and 4% in Egypt [11]. On the other hand, the rate of 10.1% hypertensive black Bantu Congolese children in this study is intermediate between those from non-Bantu Sudanese and Egyptian children [5, 11] and that of 29.4% black Bantu South African children [6]. These differences are related to standards of developing or emerging economies, overweight/obesity [1719], and ethnic/genetic factors [3, 22].…”
Section: Discussionmentioning
confidence: 60%
“…Truter et al [21] analysed children aged 9 -13 years (N=280) from various socioeconomic strata and indicated an overweight and obesity prevalence rate of 15.5% and 6.5%, respectively. Kemp et al [22] analysed the BMI values of 7-year-old children (N=816) from lower socioeconomic areas and reported that 7.8% of the participants were overweight and 3.8% were obese. Both of these studies used previous methods of arbitrarily defined percentile cut-offs and smaller sample sizes with variation in variables.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies used previous methods of arbitrarily defined percentile cut-offs and smaller sample sizes with variation in variables. [21,22] The perception currently exists that rural children from impoverished environments have lower prevalence of obesity and overweight than their counterparts with higher socioeconomic status; [19] however, more scientific evidence, including studies with larger sample sizes, equivalent variables and the use of internationally accepted BMI criteria, are needed to confirm this trend in SA. The HDI [20] categorises SA as a country in transition, similar to Algeria, Egypt, China and India; therefore it is relevant to make a comparison with international studies.…”
Section: Discussionmentioning
confidence: 99%
“…A stratified random sample of schools and educational districts in the NWP of SA was used and the process is described in detail elsewhere (Kemp et al . ). The regions and schools were chosen randomly with respect to population density and SES (from Quintile 1 – schools in poorest socio‐economic areas, to Quintile 5 – schools in areas with the highest SES).…”
Section: Methodsmentioning
confidence: 97%